2019
DOI: 10.1155/2019/4705247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moxibustion on HIF-1α and VEGF Levels in Patients with Rheumatoid Arthritis

Abstract: Background. Moxibustion has a therapeutic effect of reducing swelling and relieving pain in patients with rheumatoid arthritis (RA) but its mechanism is uncertain. Objective. To evaluate the effect of moxibustion on serum levels of hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) in patients with RA and to explore the possible mechanism of moxibustion. Methods. This study involved 46 RA patients who had fulfilled the inclusion criteria and were randomly assigned to a treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Most of the studies on the efficacy and mechanism of moxibustion are laboratory studies, and there are relatively few studies on clinical mechanism. Therefore, we have begun to study the clinical mechanism in recent years [ 21 , 22 ]; this research chooses MMP-1, MMP-3, and VEGF as the research objects, which is helpful to further reveal the effective mechanism of moxibustion in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on the efficacy and mechanism of moxibustion are laboratory studies, and there are relatively few studies on clinical mechanism. Therefore, we have begun to study the clinical mechanism in recent years [ 21 , 22 ]; this research chooses MMP-1, MMP-3, and VEGF as the research objects, which is helpful to further reveal the effective mechanism of moxibustion in the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…ST36 and BL23 are commonly used for acupuncture and moxibustion in the treatment of RA. Our previous basic researches and clinical studies have shown that moxibustion at ST36, BL23, and Ashi points can significantly improve the clinical symptoms of RA patients, and its mechanism may be related to the regulation of cytokines and signal pathways, such as IL-1 β , TNF- α , HIF-1 α , and NF- kB [ 22 , 23 ]. Besides, some studies have confirmed that moxibustion at ST36 and BL23 could improve synovitis by regulating the RANKL/OPG signaling pathway and IL-17 [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis indicated that moxibustion has certain effects on the amelioration of the inflammation in animal models with RA, including the downregulation of the level of proinflammatory cytokines and the upregulation of the level of anti-inflammatory cytokines at the same time. Clinical trials revealed that moxibustion can enhance the anti-inflammatory and analgesic effects of conventional medicine and downregulate HIF-1 α /VEGF contents to inhibit angiogenesis [ 33 ]. The conclusion is similar to the previous clinical meta-analysis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The signi cant effects of moxibustion on pain in patients with RA have been reported in various conclusions, but the effects on in ammatory factors in RA were unclear. Moxibustion enhanced the analgesic effects and anti-in ammatory of traditional and can enhance the effect of traditional medicine, reduce HIF-1α/VEGF contents to inhibit angiogenesis [18] .…”
Section: Description Of the Interventionmentioning
confidence: 99%